OPTIMALISASI INTERACTIVE FLAT PANEL (IFP) SEBAGAI MEDIA PEMBELAJARAN AUDIOVISUAL INTERAKTIF UNTUK ANAK USIA DINI - Aeni Latifah; Resty Fauziah; Rahma Adenisa; Aida sulistiani Lucky; Leni Nuraeni; Annida Luthfiyatunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of technology in early childhood education has become an important effort to improve the quality of learning. One of the emerging tools is the Interactive Flat Panel (IFP), a touchscreen device that supports interactive audiovisual learning. This study aims to describe the use of IFP in early childhood classrooms and to analyze spelling errors found in digital learning resources. This research applies a qualitative approach using literature study and content analysis. Data were collected from scientific articles, books, and selected online news related to early childhood education. The data were analyzed based on the Indonesian Spelling System (EBI). The findings indicate that IFP enhances children's engagement, making them more focused, active, and enthusiastic during learning activities. However, various spelling errors are still found in digital media, including incorrect word usage, punctuation, and sentence structure. Therefore, improving both digital and linguistic literacy is necessary to produce effective and accurate educational content.